Theoretical Foundations Of The Technology Of Media Education - Khurshid Nekboev (International Journal of Advanced Science and Technology, 2020)
This article focuses on the theoretical foundations of media education: defining the purpose of media education in the capacity of a person to reason independently of their critical arguments; to develop logical and critical thinking, to teach the media various forms of expression, to showcase their creative abilities in the media. implementation through development.